DIVISION OF A MONOPOLIST AS AN ELEMENT OF THE SYSTEM OF CONTROL OVER ECONOMIC CONCENTRATIONS IN UKRAINE AND THE EU - Борсук, Наталія (SWorldJournal, 2026)
The paper analyzes the legal regulation of the division of a business entity in Ukraine and the European Union. Based on practical cases, the issue of applying forced division to a monopolist abusing its position is highlighted. The paper substantiates t